Letter to the Editor – “Guidelines for Management of Patients with Hidradenitis Suppurativa”: The Importance of Collaboration with Infectious Diseases - Matos, João; Furtado, Isabel; Torres, Tiago; Vasconcelos, António Ludgero; Araújo Abreu, Miguel (Acta Médica Portuguesa, 2024)
N/a.